PENGARUH PROMOSI BERBASIS MEDIA SOSIAL INSTAGRAM DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Relita, Dessy Triana; Katarina, Katarina; Sore, Avelius Dominggus (STKIP Persada Khatulistiwa Sintang, 2025)
In facing many competitors offering similar products, an entrepreneur needs to maintain customer loyalty by offering quality products and optimizing sales promotions. This study aims to determine the effect of Instagram social media-based promotion and product quality on purchasing decisions at the Velvet Sintang store. The method used in this study is assisted by multiple linear regression. The study population is all consumers of the Sintang Velvet store, while the sample is 112 people using nonprobability sampling techniques in the form of incidental samples. The data was analyzed using several classical assumption tests which included normality testing using the Kolomogrov-Sminrnov test, linearity test and multicollinearity test. contribution testing includes multiple regression test, multiple correlation test, R2 determination test and effective contribution (SE) and relative contribution (SR). Hypothesis testing includes t test (partial) and f test (simultaneous). with the help of the SPSS 26 program. From the results of the study, it can be concluded that there is an influence of social media promotion, social media, Instagram, partial and simultaneous product quality, there are purchase decisions at the Sintang velvet store. The magnitude of the R square is 0.740 or 74% and 26 is influenced by other variables.